KOMITMEN AUDITOR SEBAGAI PEMODERASI PENGARUH PENGALAMAN PADA KUALITAS AUDIT - Pratiwi, Ida Ayu Dwi Laksmi; Suardana, Ketut Alit (E-Jurnal Akuntansi, 2016)
Auditor's experience is one of factors identifying errors in the analytical process. Who have more experience on the financial statements would be able to provide a reasonable explanation for the error client's financial statements and impact on audit quality. In reality, experienced auditor can also make fraud. This is thought to be influenced by the auditor's commitment. This study was conducted to determine the effect of auditor experience on audit quality and auditor’s commitment as a moderating influence. Population was all auditors working in the KAP. Sampling technique used purposive. The analytical method used is ordinary least squares and MRA. From this research it was found that the auditor's experience a positive effect on audit quality, commitment organization is not able to moderate relationship of experience in audit quality. Professional commitment is able to strengthen relationship of experience in audit quality.
Keywords: Experience, Commitment Auditor, Audit Quality